Effects of Soybean and Olive Oil Additives on the Physical and Frictional Properties of Synthetic 5W/30 Oil - Fachri Musakhi; Adhes Gamayel (Journal of Global Engineering Research and Science, 2025)
The growing demand for environmentally friendly lubricants has encouraged the development of bio-based additives derived from vegetable oils. This study investigates the effects of blending soybean oil and olive oil with SAE 5W/30 synthetic lubricant on physical properties and tribological performance. Lubricant blends were prepared with varying volume fractions of soybean oil and olive oil (0, 20, 40, 60, and 100%). Density and kinematic viscosity were measured at room temperature to evaluate changes in physical properties. Tribological behavior was examined using a pin-on-disc friction test under controlled conditions, including a constant rotational speed of 450 rpm, a normal load of 2 kg, and a test duration of 3 minutes. Friction temperature was recorded during testing, and wear surface morphology was analyzed using optical microscopy. The results indicate that increasing vegetable oil content influences density and viscosity, reflecting modifications in lubricant film characteristics. Blended lubricants generally exhibited lower friction temperatures compared to pure synthetic oil, indicating improved lubricity and heat dissipation. Surface morphology observations revealed smoother worn surfaces and reduced wear severity for blended oils, particularly those containing balanced proportions of soybean and olive oil. These improvements are attributed to the polar functional groups in vegetable oils, which enhance adsorption and film formation at the contact interface. Overall, the findings demonstrate that soybean and olive oil blends can effectively improve the tribological performance of SAE 5W/30 synthetic lubricant, highlighting their potential as sustainable and eco-friendly lubricant additives for mechanical applications.